Bonhomme : French Canadian stories and sketches - Walsh, Henry Cecil (University of Toronto Press, Scholarly Publishing Division, 1973)
A part of the Toronto Reprint Library of Canadian Prose and Poetry Series, this series is intended to provide for libraries a varied selection of titles of Canadian prose and poetry which have been long out-of-print. All form part of Canada's literary history: all help to provide a better knowledge of our cultural and social past.